Dual photoluminescence and charge transport in an alkoxy biphenyl benzoate ferroelectric liquid crystalline–graphene oxide composite. (18th September 2018) - Singh, Dharmendra Pratap; Duponchel, Benoit; Boussoualem, Yahia; Agrahari, Kaushlendra; Manohar, Rajiv; Kumar, Veeresh; Pasricha, Renu; Pujar, Gonibasappa H.; Inamdar, Sanjeev R.; Douali, Redouane; Daoudi, Abdelylah
Abstract : GO has been dispersed in a ferroelectric liquid crystalline material to prepare a FLC–GO composite. Abstract : An optimized concentration of graphene oxide (GO) has been dispersed in a ferroelectric liquid crystalline (FLC) material namely 4′-(octyloxy)-[1, 1′-biphenyl]-4-yl 4-(heptan-2-yloxy)benzoate, to prepare a FLC–GO composite. Temperature dependent photoluminescence (PL) measurements for the FLC–GO composite were conducted between 30–100 °C. We observed a superlinear increase in the PL with increasing temperature. The time resolved luminescence study exhibits a bi-exponential decay time with a shorter life time for the FLC–GO composite and confirms the surface energy transfer from GO to FLC. Charge transport and current–voltage ( I – V ) characteristics for the FLC–GO composite have been investigated at ambient conditions by using current sensing atomic force microscopy. For the FLC–GO composite, critical diode like nonlinear I – V curves have been obtained in which the charge transport is assigned to the thermally active intermolecular hopping at room temperature. The FLC material yields ionic charge mobilities of 1.45 × 10 −5, 1.26 × 10 −5 and 9.83 × 10 −6 cm 2 V −1 s −1 in isotropic, chiral nematic (N*) and chiral smectic C (SmC*) phases. The dispersion of GO significantly enhances the ionic mobility in the composite which was observed to be 2.71 × 10 −4, 2.69 × 10 −4 and 2.65 × 10 −4 cm 2 V −1 s −1 for the aforementioned phase sequence. Physical interactions between GO and FLC molecules were confirmed by FTIR and polarized optical microscopy. In-plane coupling between the orientation of GO and the long molecular axis of the FLC molecules remarkably enhances the band intensity of CO, C–H, COO, C–O and C–H vibrations. The size of multi-domain fan texture in the SmC* phase has been enhanced after the dispersion of GO. The cobweb like networking in the oily streaks texture of the N* phase confirms the interesting molecular architecture via planar anchoring between FLC molecules and GO. This work opens new avenues towards applications in pico-ampere current-regulated electronic devices and opto-electronics.